2017
DOI: 10.3390/e19020065
|View full text |Cite
|
Sign up to set email alerts
|

An Android Malicious Code Detection Method Based on Improved DCA Algorithm

Abstract: Abstract:Recently, Android malicious code has increased dramatically and the technology of reinforcement is increasingly powerful. Due to the development of code obfuscation and polymorphic deformation technology, the current Android malicious code static detection method whose feature selected is the semantic of application source code can not completely extract malware's code features. The Android malware static detection methods whose features used are only obtained from the AndroidManifest.xml file are eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…From Figure 9, it can be concluded that the IDT algorithm proposed in this paper has significantly improved the accuracy of the algorithm compared with the traditional C4.5 algorithm. Compared with the algorithm in Wang et al, 10 the IDT algorithm proposed in this paper still improves in terms of accuracy. The smaller the redundancy between attributes in the data set, the more significant the accuracy improvement is.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 87%
See 3 more Smart Citations
“…From Figure 9, it can be concluded that the IDT algorithm proposed in this paper has significantly improved the accuracy of the algorithm compared with the traditional C4.5 algorithm. Compared with the algorithm in Wang et al, 10 the IDT algorithm proposed in this paper still improves in terms of accuracy. The smaller the redundancy between attributes in the data set, the more significant the accuracy improvement is.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 87%
“…Experiment 2: The improved C4.5 algorithm (Improved Decision Tree Algorithm for short: IDT algorithm) is validated with 10 times cross‐validation, and the average classification accuracy is used as a criterion for validation. The data set is the same as that of Experiment 1 and compared with the traditional decision tree algorithm and the SU_C4.5 algorithm proposed in Wang et al 10 The experimental results are shown in Figure 9.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 99%
See 2 more Smart Citations